2017
DOI: 10.17509/jaset.v9i1.5258
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengungkapan CSR Terhadap Pelaporan Pajak Agresif, Dan Pengaruhnya Terhadap Return Saham

Abstract: Abstract. This study examine the association between Corporate Sosial Responsibility (CSR), corporate tax-aggressiveness and stock return. It also examine moderating effect of the effectiveness of audit committee as corporate governance mechanism to the association of CSR disclosure to corporate tax-aggressiveness. Examination conducted on 173 firm-years that were selected by purposive sampling method from manufacturing firm listed at IDX from 2011-2013. By measuring the corporate tax-  aggressiveness through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…At present, public companies use the concept of the Global Reporting Initiative (GRI) as a procedure for designing CSR reports. CSR is also disclosed by the company to consider the long-term prospects in carrying out operations on the environment and communities affected by these operations [33].…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…At present, public companies use the concept of the Global Reporting Initiative (GRI) as a procedure for designing CSR reports. CSR is also disclosed by the company to consider the long-term prospects in carrying out operations on the environment and communities affected by these operations [33].…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%
“…A financial behavioral survey conducted by Baptista and Dewi (2021) found that financial literacy was closely related to financial management, and higher financial literacy among MSMEs led to better corporate governance. In this case, financial literacy is the ability to understand and analyze financial options, plan for the future, and respond appropriately to events (Anis, 2017).…”
Section: Introductionmentioning
confidence: 99%